Cigarette smoke and decreased oxygen tension inhibit pulmonary claudin-6 expression. (25th November 2016) - Jimenez, Felix R.; Lewis, Josh B.; Belgique, Samuel T.; Milner, Dallin C.; Lewis, Adam L.; Dunaway, Todd M.; Egbert, Kaleb M.; Winden, Duane R.; Arroyo, Juan A.; Reynolds, Paul R.
ABSTRACT: Purpose : Chronic obstructive pulmonary disease is a condition involving perturbed barrier integrity coincident with both emphysema and inflammation of the airways, and smoking is considered a major risk factor. Claudins (Cldns) stabilize barriers and contribute to tight junctions by preventing paracellular transport of extracellular fluid constituents.Methods : To determine Cldn6 was differentially influenced by tobacco smoke, Cldn6 was evaluated in cells and tissues by q-PCR, immunoblotting, and immunohistochemistry following exposure. Cldn6 transcriptional regulation was also assessed using luciferase reporter constructs.Results : Q-PCR and immunoblotting revealed that Cldn6 was decreased in alveolar type II-like epithelial cells (A549) and primary small airway epithelial cells when exposed to cigarette smoke extract (CSE). Cldn6 was also markedly decreased in the lungs of mice exposed to acute tobacco smoke delivered by a nose-only automated smoke machine compared to controls. Luciferase reporter assays incorporating 0.5-kb, 1.0-kb, or 2.0-kb of the Cldn6 promoter revealed decreased transcription of Cldn6 following exposure to CSE. Cldn6 transcriptional regulation was also assessed in hypoxic conditions due to low oxygen tension observed during smoking. Hypoxia and hypoxia inducible factor-1 alpha caused decreased transcription of the Cldn6 gene via interactions with putative response elements in the proximal promoter sequence.Conclusions : These data reveal that tight junctional proteins such as Cldn6 are differentially regulated by tobacco-smoke exposure and that Cldns are potentially targeted when epithelial cells respond to tobacco smoke. Further research may show that Cldns expressed in tight junctions between parenchymal cells contribute to impaired structural integrity of the lung coincident with smoking.